Enzyme-instructed morphology transformation of mitochondria-targeting peptide for the selective eradication of osteosarcoma. Issue 12 (17th October 2022) - Jeena, M. T.; Jin, Seongeon; Jana, Batakrishna; Ryu, Ja-Hyoung
Abstract : Enzyme instructed morphology transformation for selective cancer therapy. Due to the response of alkaline phosphatase, micelle was disassembled into a monomer, it internalized to the cell and induced mitochondrial dysfunction through self-assembly. Abstract : The treatment of osteosarcoma involves an adjuvant therapy that combines surgery and chemotherapy. However, considering that children are the main victims of osteosarcoma, replacing such a harsh treatment with a soft but powerful method that ensures a complete cure while having no adverse effects is highly desirable. To achieve this aim, we have developed a supramolecular therapeutic strategy based on morphology-transformable mitochondria-targeting peptides for the eradication of osteosarcoma with enhanced selectivity and reduced side effects. A newly designed micelle-forming amphiphilic peptide, l -Mito-FFYp, consisting of a phosphate substrate for the biomarker enzyme of osteosarcoma alkaline phosphatase (ALP), disassembles in response to the ALP enzyme in the cell membrane to generate positively charged l -Mito-FFY molecules, which diffuse inside the targeted cell and self-assemble to form nanostructures specifically inside the mitochondria to induce cell apoptosis.